Nomenclatural notes in Polanisia (Cleomaceae) - Roalson, Eric H. (Phytotaxa, 2020)
Polanisia (Cleomaceae) includes 8 taxa in 5 species distributed through much of North America. A full nomenclatural synonymy is presented including two lectotypes and one neotype.